Theoretical and experimental studies of battened buckling-restrained braces. (1st April 2017) - Guo, Yan-Lin; Zhang, Bo-Hao; Zhu, Bo-Li; Zhou, Peng; Zhang, You-Hao; Tong, Jing-Zhong
Highlights: A battened buckling-restrained brace (B-RBB) is proposed. An interaction formula is proposed for predicting ultimate load-carrying capacity of B-BRBs. Ultimate resistance and failure modes of B-BRBs are investigated numerically. Hysteretic responses of B-BRBs are explored through FE analysis. Hysteretic responses of five B-BRB specimens are experimentally investigated. Abstract: A new type of core-separated buckling-restrained braces, namely a core-separated battened buckling-restrained brace (B-BRB) has been proposed. Its load-carrying capacity and hysteretic response are investigated theoretically and experimentally in this paper. The B-BRB has a remarkable advantage over a common buckling-restrained brace (BRB), in which the newly formed cross-section of the B-BRB is spread outwards by spacing two cores, hence resulting in higher material utilization efficiency in its structural design. In addition, the two independent all-steel BRBs, each having a single plate core simply in-filled in a narrow hollow section, are connected by longitudinally distributed battens rather than continuous plates. Based on the elastic-plastic FE analysis of a B-BRB under monotonic compressive load, its ultimate resistance and failure modes are investigated numerically, considering the effect of its overall initial geometric imperfection. An interaction formula between normalized slenderness ratio and buckling factor of the B-BRB is proposed for predicting its ultimate load-carrying capacity. Consequently, the hysteretic response of the B-BRB is explored through elastic-plastic FE analysis. The maximum normalized slenderness ratios of the B-BRBs required for a load-bearing type and an energy-dissipation type are proposed in their strength designs, respectively. Ultimately, hysteretic responses of five B-BRB specimens have been experimentally investigated. The experimental results are compared with the FE numerical analysis, which considers plate local buckling of all components of the B-BRBs. The comparison has verified the rationality of the proposed design method.